Analog-to-digital converter based on single-electron tunneling transistors. - Chaohong Hu (IEEE Transactions on VLSI systems)
A novel single-electron tunneling transistors (SETTs) based analog-to-digital converter (ADC) is proposed in this paper. The scheme we propose fully utilizes Coulomb oscillation effect, can properly operate at T>0 K, and only a capacitive divider (built with 2n-2 capacitors) and n pairs of complementary SETTs are required for an n-bit ADC implementation. When compared with other state-of-the-art SET based ADCs our method provides the most compact solution measured in terms of circuit elements and has a potential advantage in terms of conversion speed. To illustrate the operation of the proposed scheme, a 4-bit ADC is demonstrated at 10K by means of simulation.